Perbandingan Kinerja Haproxy dan Zevenet Dalam Pengimplementasian Multi Service Load Balancing - Faris Muslim Azmi; Mahendra Data; Heru Nurwasityo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The development of information technology has been growth rapidly over time thus escalated the needs for information services. Each user has different needs of information services. Thus, a multi-service load balancing system is required to minimize traffic congestion and to reduce server's workloads. Load balancing is a computer network method to distribute loads on servers. HAproxy and Zevenet are load balancers that support various services such as HTTP and FTP. In this research, the conducted test is performance comparison of HAproxy and Zevenet in the implementation of multi-service load balancing. Performance testing is done by sending 1000, 2500 and 5000 HTTP and FTP connections on both HAproxy and Zevenet. The algorithms used in this test are round robin and least connection and the experiments parameter which is used are response time and resource utilization. Based on the performances test result, both on HTTP and FTP services, HAproxy showed better test results on the response time parameter. While Zevenet showed superior test results on resource utilization parameter on both HTTP and FTP services.